Stakeholder perspectives on proposed policies to improve distribution and retention of doctors in rural areas of Uttar Pradesh, India - Veena Sriram; Shreya Hariyani; Ummekulsoom Lalani; Ravi Teja Buddhiraju; Pooja Pandey; Sara Bennett (BMC, 2021)
Abstract Background In India, the distribution and retention of biomedical doctors in public sector facilities in rural areas is an obstacle to improving access to health services. The Government of Uttar Pradesh is developing a comprehensive, ten-year Human Resources for Health (HRH) strategy, which includes policies to address rural distribution and retention of government doctors in Uttar Pradesh (UP). We undertook a stakeholder analysis to understand stakeholder positions on particular policies within the strategy, and to examine how stakeholder power and interests would shape the development and implementation of these proposed policies. This paper focuses on the results of the stakeholder analysis pertaining to rural distribution and retention of doctors in the government sector in UP. Our objectives are to 1) analyze stakeholder power in influencing the adoption of policies; 2) compare and analyze stakeholder positions on specific policies, including their perspectives on the conditions for successful policy adoption and implementation; and 3) explore the challenges with developing and implementing a coordinated, 'bundled' approach to strengthening rural distribution and retention of doctors. Methods We utilized three forms of data collection for this study - document review, in-depth interviews and focus group discussions. We conducted 17 interviews and three focus group discussions with key stakeholders between September and November 2019. Results We found that the adoption of a coordinated policy approach for rural retention and distribution of doctors is negatively impacted by governance challenges and fragmentation within and beyond the health sector. Respondents also noted that the opposition to certain policies by health worker associations created challenges for comprehensive policy development. Finally, respondents believed that even in the event of policy adoption, implementation remained severely hampered by several factors, including weak mechanisms of accountability and perceived corruption at local, district and state level. Conclusion Building on the findings of this analysis, we propose several strategies for addressing the challenges in improving access to government doctors in rural areas of UP, including additional policies that address key concerns raised by stakeholders, and improved mechanisms for coordination, accountability and transparency.